Analisis Pengaruh Penambahan Octane Booster Dengan Bahan Bakar Pertalite Terhadap Emisi Gas Buang - Yusuf Prasetya Darmawan; Rozan Alifiyan Darmawan; Reny Susanti; Evan Hardi Nurul Huda; Trisma Jaya Saputra (Pusat Riset dan Inovasi Nasional, 2023)
Vehicles are the main thing in supporting daily activities. Currently, motorized vehicles are a necessity for the community. This increase in vehicle volume leads to an increase in air pollution due to exhaust emissions. The use of low-octane fuel will affect emissions and overall motor performance. One way to increase octane number is to give octane booster. This research was conducted to see the impact of adding octane booster on exhaust emissions. Exhaust emission tests are carried out to see the value of CO, CO2 and HC. In its implementation, the author uses a Megapro PGM-FI motorcycle with 150 cc. The test results resulted in the lowest CO content of 0.19% in pure pertalite fuel, the lowest CO2 of 3.10% in the addition of 3 ml octane booster, and the lowest HC of 213 ppm in the addition of 7 ml octane booster. While the highest CO content was 0.23% in the addition of 7 ml octane booster, the highest CO2 of 3.10% in the addition of 7 ml octane booster and in pure pertalite fuel, and the highest HC of 247 ppm in pure pertalite fuel.